FUTURE SCENARIO OF PHRAPARIYATTIDHAMMA EDUCATION ADMINISTRATION IN DHAMMA SECTION OF THAI SANGHA - Thitavaro (Iemdee), PhraAtikhun; Ruangsanka, Rawing; Siriwan, Intha (Journal of Educational Review Faculty of Education in MCU, 2021)
This research paper aimed to propose the scenario of Phrapariyattidhamma education administration in Dhamma section of Thai Sangha. Mixed methods research divided into 3 steps was designed which consisted of 1) study information from academic documents related research and interview 12 key informants by using purposive sampling. 2) Synthesis and develop research results by using focus group discussion with 9 experts. 3) The research results were examined by using a questionnaire with the sample group of 148 school administrators. Statistics used for data analysis was mean, percentage and standard deviation. The research results showed the scenario of Phrapariyattidhamma education administration in Dhamma section of Thai Sangha consisted of 5 scenarios which were Scenario 1: decentralized (decentralized management with direction to the region), Scenario 2: Strengthening (build the fundamental of Phrapariyattidhamma education administration to be strengthened), Scenario 3: Build a foundation (Build a foundation for national growth with a policy that promotes the education of Dharma as the basis of life), Scenario 4: Enhancement (enhances the characteristics of teachers and determines the desirable characteristics of the learner) and Scenario 5: Sustainability (provides the education of Phrapariyattidhamma education administration in Dhamma section for sustainable).